Halal certification for small scale enterprise in Indonesia: policy changing impacts - Moh Zaenal Abidin Eko Putro,; Suhanah,; M.Fakhruddin,; Asnawati Mardamin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Through the Law No 33/2014 about Halal Product Assurance, Indonesian government has just implemented halal certification system which mandates all halal related business owners including small scale business owners to gain halal certificate letter issued by halal’ state body. This new policy changed the previous halal permission that was proposed voluntarily. It also reduced the role of the previous halal body, namely Lembaga Pengkajian Pangan Obat-obatan dan Kosmetika Majelis Ulama Indonesia (LPPOM MUI, or Assessment Institute for Foods, Drugs, and Cosmetics of The Indonesian Council of Ulama) that previously seemed dominantly body of halal certification permission. This paper tries to explore the halal certification for small scale business owners in Indonesia. Being stemmed from qualitative research that combines several data gathering techniques such as in-depth interview, study literature as well as observation, this research shows that the policy changing of halal certification still less attracted small-scale business owners although it was conducted by free of charge. Latterly, it becomes problematic caused by the digitalization of halal certificate permission.